PENEGAKAN SANKSI DALAM HUKUM PIDANA TERHADAP PELAKU PERUSAKAN HUTAN - Pasolang, Maryanto Mantong (Universitas Tadulako, 2020)
Forest destruction in Indonesia is threatened by severe sanctions in criminal law, because it is a forestry crime regulated on Article 12, 14, 15, 16, 17, 19-28 in Law number 18 of 2013 that concerning prevention and eradication of forest destruction. The legal instrument is expected to sanction to prevent and combat forest destruction in Indonesia. But the fact shows that the deforestation rate in the last five years forest destruction in Indonesia has reached 2.83 million ha per year. In Central Sulawesi of 2014, forest damage caused by fires was 70.73 ha. The consequence would certainly be the problem of how the role of enforcement of sanctions in criminal law to perpetrators of forest destruction.The research methods were statute approach and conceptual approach with normative legal type research and the source of legal materials were primary, secondary and tertiary, which is supported by sociological juridical research, and content analysis.The results of this research show the criminal sanction system adopted in the law on the prevention and eradication of forest destruction is a cumulative system, with the threat of maximum and minimum penalties. The threat of punishment (sanctions) is quite severe, but it is very dependent on the integrity of law enforcement in implementing criminal sanctions against perpetrators of forest destruction, because there is still a tendency for the weak enforcement of witnesses (punishments) to perpetrators of forest destruction.Enforcement of criminal law witnesses in terms of forest destruction is still strongly influenced by several factors that are closely related to the factors of effectiveness of law enforcement such as: Law, Implementing Law, Facilities and Community Legal Awareness/Culture. Other factors that influence the enforcement of legal sanctions are still weak coordination between law enforcers (Police, Prosecutors and Courts) so that it is very vulnerable to creating conflicts of interest. This is one of the obstacles in the enforcement of criminal acts in the forestry sector. And the influence on application of criminal sanctions to perpetrators of forest destruction because they are still oriented to the principle of ultimum remedium which should use primum remedium (as the main way) because the act of forest destruction is an act that can directly or indirectly endanger the humans lives.